The theory-practice research gains from big data - Rita, Paulo (2023)
Rita, P., Tiago, M. T. B., & Caetano, J. (2023). The theory-practice research gains from big data: Evidence from hospitality loyalty programs. International Journal of Contemporary Hospitality Management. https://doi.org/10.1108/IJCHM-05-2022-0646 --- This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project – UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS, research grants UIDB/04521/2020 of the Advance/CSG, ISEG – Lisbon School of Economics and Management; and UIDB/00685/2020 of the Centre of Applied Economics Studies of the Atlantic, School of Business and Economics of the University of the Azores. ---%ABS3%